ACG Clinical Guidelines: Clinical Use of Esophageal Physiologic Testing. (5th September 2020) - Gyawali, C. Prakash; Carlson, Dustin A.; Chen, Joan W.; Patel, Amit; Wong, Robert J.; Yadlapati, Rena H.
Abstract : Esophageal symptoms are common and may indicate the presence of gastroesophageal reflux disease (GERD), structural processes, motor dysfunction, behavioral conditions, or functional disorders. Esophageal physiologic tests are often performed when initial endoscopic evaluation is unrevealing, especially when symptoms persist despite empiric management. Commonly used esophageal physiologic tests include esophageal manometry, ambulatory reflux monitoring, and barium esophagram. Functional lumen imaging probe (FLIP) has recently been approved for the evaluation of esophageal pressure and dimensions using volumetric distension of a catheter-mounted balloon and as an adjunctive test for the evaluation of symptoms suggestive of motor dysfunction. Targeted utilization of esophageal physiologic tests can lead to definitive diagnosis of esophageal disorders but can also help rule out organic disorders while making a diagnosis of functional esophageal disorders. Esophageal physiologic tests can evaluate obstructive symptoms (dysphagia and regurgitation), typical and atypical GERD symptoms, and behavioral symptoms (belching and rumination). Certain parameters from esophageal physiologic tests can help guide the management of GERD and predict outcomes. In this ACG clinical guideline, we used the Grading of Recommendations Assessment, Development and Evaluation process to describe performance characteristics and clinical value of esophageal physiologic tests and provide recommendations for their utilization in routine clinical practice.